2002
DOI: 10.1242/dev.00164
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled 2 is essential for cardiac outflow tract development, somite segmentation and neural tube closure

Abstract: The murine dishevelled 2 (Dvl2) gene is an ortholog of theDrosophila segment polarity gene Dishevelled, a member of the highly conserved Wingless/Wnt developmental pathway.Dvl2-deficient mice were produced to determine the role ofDvl2 in mammalian development. Mice containing null mutations inDvl2 present with 50% lethality in both inbred 129S6 and in a hybrid 129S6-NIH Black Swiss background because of severe cardiovascular outflow tract defects, including double outlet right ventricle, transposition of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
322
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(338 citation statements)
references
References 66 publications
15
322
1
Order By: Relevance
“…The Fz3 mutation on a 129/SVJ x C57BL6 background shows a small percentage of exencephaly, which appears to be dependent on modifiers . Embryos deficient in Dvl2 show a low percentage of exencephaly and spina bifida, whereas most Dvl1 À/À ; Dvl2 À/À double mutants show craniorachischisis on a 129SvEv inbred strain and a mixed 129SvEv x NIH Black Swiss strain (Hamblet et al, 2002). Other combined mutations have also shown a percentage of exencephaly, including Dvl3 6 ; Vangl2 Lpþ (5 cranio, 2 exen /22), whereas Dvl3 À/À ; Vangl2 Lp/þ showed only craniorachischisis (6/16) on a mixed genetic background with 129S6 (Etheridge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fz3 mutation on a 129/SVJ x C57BL6 background shows a small percentage of exencephaly, which appears to be dependent on modifiers . Embryos deficient in Dvl2 show a low percentage of exencephaly and spina bifida, whereas most Dvl1 À/À ; Dvl2 À/À double mutants show craniorachischisis on a 129SvEv inbred strain and a mixed 129SvEv x NIH Black Swiss strain (Hamblet et al, 2002). Other combined mutations have also shown a percentage of exencephaly, including Dvl3 6 ; Vangl2 Lpþ (5 cranio, 2 exen /22), whereas Dvl3 À/À ; Vangl2 Lp/þ showed only craniorachischisis (6/16) on a mixed genetic background with 129S6 (Etheridge et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…PCP has also been implicated in the cell movements that form the eyelid (Murdoch et al, 2001;Wang and Nathans, 2007). Defects in PCP genes constitute approximately 5% of all known murine NTD mutations and are usually associated with craniorachischisis (a lack of neural tube closure throughout its length), open eyelids, and rotational defects of the cochlear sensory cells (Kibar et al, 2001;Murdoch et al, 2001;Hamblet et al, 2002;Curtin et al, 2003;Montcouquiol et al, 2003;Lu et al, 2004;Wang et al, 2006b;Harris and Juriloff, 2007;Torban et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Pnn hypomorphs exhibited a complex phenotype. Intriguingly, all of these phenotypes-vertebral patterning (Ikeya and Takada, 2001;Aulehla et al, 2003), dorsal dermis development (Olivera-Martinez et al, 2001, BAT formation (Atit et al, 2006), and palate and outflow tract development (Hamblet et al, 2002;Hutson and Kirby, 2003;Schmidt and Patel, 2005)-have been observed in mice having defects in Wnt/␤-catenin signaling. This finding raised an interesting possibility that PNN might be involved in the regulation of Wnt/␤-catenin signaling during mouse development.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos positive for Math1/GFP or Math1-RFP were identified by positive GFP or RFP signals in the cerebellum and spinal cord, respectively. Genotyping for Dvl1, Dvl2 knockout alleles, and the Looptail allele was carried out as described 16,[19][20] . To differentiate the Dvl2-EGFP BAC transgene from the endogenous wild-type Dvl2, a pair of primers flanking intron 2 were used for PCR (supplemental Table II).…”
Section: Mouse Strains and Animal Carementioning
confidence: 99%